Correction: Boosting the oxygen reduction activity of a three-dimensional network Co–N–C electrocatalyst via space-confined control of nitrogen-doping efficiency and the molecular-level coordination effect. Issue 46 (19th November 2018) - Guo, Chaozhong; Li, Yanrong; Liao, Wenli; Liu, Yao; Li, Zhongbin; Sun, Lingtao; Chen, Changguo; Zhang, Jin; Si, Yujun; Li, Lu
Abstract : Correction for 'Boosting the oxygen reduction activity of a three-dimensional network Co–N–C electrocatalyst via space-confined control of nitrogen-doping efficiency and the molecular-level coordination effect' by Chaozhong Guo et al., J. Mater. Chem. A, 2018, 6, 13050–13061.